(2x-3)(4y-6)=

Simple and best practice solution for (2x-3)(4y-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)(4y-6)= equation:


Simplifying
(2x + -3)(4y + -6) = 0

Reorder the terms:
(-3 + 2x)(4y + -6) = 0

Reorder the terms:
(-3 + 2x)(-6 + 4y) = 0

Multiply (-3 + 2x) * (-6 + 4y)
(-3(-6 + 4y) + 2x * (-6 + 4y)) = 0
((-6 * -3 + 4y * -3) + 2x * (-6 + 4y)) = 0
((18 + -12y) + 2x * (-6 + 4y)) = 0
(18 + -12y + (-6 * 2x + 4y * 2x)) = 0
(18 + -12y + (-12x + 8xy)) = 0

Reorder the terms:
(18 + -12x + 8xy + -12y) = 0
(18 + -12x + 8xy + -12y) = 0

Solving
18 + -12x + 8xy + -12y = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -12x + 8xy + -18 + -12y = 0 + -18

Reorder the terms:
18 + -18 + -12x + 8xy + -12y = 0 + -18

Combine like terms: 18 + -18 = 0
0 + -12x + 8xy + -12y = 0 + -18
-12x + 8xy + -12y = 0 + -18

Combine like terms: 0 + -18 = -18
-12x + 8xy + -12y = -18

Add '12y' to each side of the equation.
-12x + 8xy + -12y + 12y = -18 + 12y

Combine like terms: -12y + 12y = 0
-12x + 8xy + 0 = -18 + 12y
-12x + 8xy = -18 + 12y

Reorder the terms:
18 + -12x + 8xy + -12y = -18 + 12y + 18 + -12y

Reorder the terms:
18 + -12x + 8xy + -12y = -18 + 18 + 12y + -12y

Combine like terms: -18 + 18 = 0
18 + -12x + 8xy + -12y = 0 + 12y + -12y
18 + -12x + 8xy + -12y = 12y + -12y

Combine like terms: 12y + -12y = 0
18 + -12x + 8xy + -12y = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(9 + -6x + 4xy + -6y) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(9 + -6x + 4xy + -6y)' equal to zero and attempt to solve: Simplifying 9 + -6x + 4xy + -6y = 0 Solving 9 + -6x + 4xy + -6y = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -6x + 4xy + -9 + -6y = 0 + -9 Reorder the terms: 9 + -9 + -6x + 4xy + -6y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -6x + 4xy + -6y = 0 + -9 -6x + 4xy + -6y = 0 + -9 Combine like terms: 0 + -9 = -9 -6x + 4xy + -6y = -9 Add '6y' to each side of the equation. -6x + 4xy + -6y + 6y = -9 + 6y Combine like terms: -6y + 6y = 0 -6x + 4xy + 0 = -9 + 6y -6x + 4xy = -9 + 6y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| (x-5)(y-3)= | | 4/5*x-7/10*x=4 | | 5k^2+17k-22=0 | | (x-3)(y+6)= | | 4/15/5/7 | | -1/2x-2=0 | | P=5Q+7 | | 4x^2+19x-23=0 | | (x+2)(y+4)= | | X-94=-5x+2 | | X^4-10x-50=0 | | Y-C=S | | .5x=197125 | | .05x=197125 | | 3/11 | | -2(3n+2)=4 | | y^2+6y-28=0 | | 8(y-5)/3=-2y | | 3.14*100*h=4710 | | X(7.8-1.2)=54.2 | | (2x+13)(x-3)=0 | | Y=38+7.7x | | log(x+13)-log(2)=log(3x+3) | | 7x=28000000 | | 0.60x+0.85*30=0.30*97 | | 2(6x-13)= | | log(x+13)-log(2)=log(2x+3) | | 43-2[6+(3+2)]= | | 0.03x+0.15(70)=0.15(82) | | 2x+x+6=8 | | Sin(2x)cos(x)=sin(x)cos(2x) | | -4/5(-19/16) |

Equations solver categories